Application of Monte Carlo Simulation in Predicting Stock Prices at PT Bank Syariah Indonesia Tbk - Kamila, Isti; Anggraeni, Fidela; Ramadhany Rumengan, Novia; Dwi Puji Ramadhani, Novira; Fatanah Zetafahrul, Philant; Ananda Br Pelawi, Riva; Mawar Desember, Natalie (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2025)
Stock investment has become a popular choice for individuals seeking financial returns, although it comes with high risks due to market price volatility. This study aims to apply the Monte Carlo Simulation method to predict the stock price of PT Bank Syariah Indonesia Tbk (BRIS) and assess the accuracy of its predictions. BRIS was selected as it represents the largest Islamic bank in Indonesia and is attractive to investors focused on sharia-compliant finance. The research uses historical daily closing prices from January 2023 to December 2024, which are processed into daily returns and volatility as inputs for the simulation model based on Geometric Brownian Motion (GBM). The simulation was run three times to generate a variety of potential price paths. The predicted results were then compared with actual stock prices, and the Mean Absolute Percentage Error (MAPE) was used to evaluate prediction accuracy. The MAPE result of 39.75% indicates a moderate level of forecasting error. Although not perfectly precise, the model provides a valuable insight into possible price movements. The Monte Carlo method proves useful in capturing the uncertainty of the stock market and serves as a supportive tool for better investment decisions, especially in the Islamic banking sector. This research is expected to offer useful guidance for investors and stakeholders in managing portfolios using a quantitative approach.